The capabilities of the educational organizations in making use of tacit knowledge - Ozmen, Fatma (Elsevier Science Bv, 2010)
Educational organizations are inherently knowledge intensive organizations. The importance and management of tacit knowledge should have been understood and should have been applied in every process of the organizations. However, the researches done on knowledge management capabilities of the educational organizations have revealed unsatisfactory consequences. From the aspect of making use of tacit knowledge, this study, based on the literature review, aimed to determine the current situation of the educational organizations in general, and to clarify the obstacles faced in explicating and sharing of tacit knowledge. In the lights of implemented strategies reached through literature review, some recommendations were made. (C) 2010 Published by Elsevier Ltd.
1st World Conference on Learning, Teaching and Administration (WCLTA) -- OCT 29-31, 2010 -- Amer Univ, Cairo, EGYPT
Keywords: Knowledge management; tacit knowledge; educational organizations; competitive advantage